TELEOPERATED SYSTEM WITH ACCELEROMETERS FOR DISABILITY - Valdez, Josue Zarate; Cucho, Ruben Diaz (European Scientific Journal, ESJ, 2015)
This project involves the implementation of a teleoperated arm using an embedded platform based on a reconfigurable logic device (FPGA) configured and programmed in VHDL for Atmega 328p, using servomotors MG996R brand and a communication terminal with accelerometers, scheduled language C. the system is incompatible with teleoperated robotic autonomy (understood as the case where control and decision making are performed by the robot itself). That is why robots are teleoperated tasks perception of the environment, complex manipulation that are performed by humans and planning, ie, the operator acts in real time closed loop control high level. The evolved systems provide sensory feedback to the operator environment (strength, distance). In this manipulation we used an anthropomorphic arm with automatic controllers that replicate the movements of the operator.